(untitled) (Biological Sciences - PJSIR, 2001)
The antibacterial, antifungal and phytotoxicity tests were performed on the rnethanolic extract, etbylacetate fraction and four sterols isolated from tbe green alga Chara wallichii A. Br., collected from flood water of River Indus, near Petaro, Sindh, Pakistan. The compounds named as cholesterol (1), clerosterol (2), stigmasterol (3) and j3-sitosterol (4) bave been isolated for the first time from this alga and their antimicrobial activities as well as phytotoxicity studies are being reported.